The occupation of the Mucuri Valley: the rural elite and the dilemma between modernity and backwardness (Revista Espinhaço, 2020)
Before the 19th century, the Mucuri Valley, Northeast of Minas Gerais state, Brazil, was populated by dispersed indigenous communities. This scenario has undergone significant changes since that date, with an intense population flow due to a high degree of commercialization that occurred after the mining crisis. The aim of this study is to analyze the particularities and the results of the occupation that occurred in the Mucuri Valley from the second half of the 19th century to the middle of the 20th century. The Mucuri underwent a colonization process with its large-scale production based on coffee production, later, on livestock. The agrego was the main labor force of medium and large rural properties, used for uninterrupted deforestation for the benefit of crops and pasture. As a result, I find that the predatory exploitation of the Mucuri forests combined with an expressive contingent of households in miserable conditions generated wealth for rural landowners, but did not stimulate technological investments typical of the capitalist model, bringing through the press a representation of the ambiguous region, coexisting prosperity and ruin.
Keywords: Mucuri Valley; Agriculture regime; Aggregation; Predatory Culture